CORRELATION BETWEEN STRESS AND TEMPOROMANDIBULAR DISORDER IN ORPHANED ADOLESCENT IN BANJARMASIN - Fellbyan Fellbyan; Rahmad Arifin; Galuh Dwinta Sari (FKG Unlam, 2020)
ABSTRACTBackground: Temporomandibular disorder is a temporomandibular joint disturbance characterized with the pain in masticatory muscle and TMJ; clicking in TMJ; and deflection, deviation pattern with limitation in opening of the mouth. TMD can be found in adolescents with prevalence and severity increased along with the age. TMD in adolescent was caused by the increased of the masticatory muscle activity. In adolescent, it was caused by the increase of the emotional state especially stress. Stress is a condition that often experienced by every people including orphaned adolescent, who has more problems than the other adolescent. Purpose: The aim of this study was to analyze the correlation between stress and temporomandibular disorder in orphaned adolescent in Banjarmasin. Method: This study is an analytical observational research with cross sectional design. The study was involving 13-18 years old orphaned adolescents in Banjarmasin with purposive sampling. This study is using PSS for stress examination and RDC/TMD for TMD examination. The correlation between stress and TMD were analyzed with Spearman analysis test. Results: This research showed that 61% of the subject had moderate stress level and TMD was found in 68.3% of the subject, which consists of 58.5% had myofascial pain and 9.8% had disc displacement. Spearman analysis test showed that there is statistical correlation between stress and temporomandibular disorder in orphaned adolescent in Banjarmasin (p<0.05). Conclusion: There is a correlation between stress and temporomandibular disorder in orphaned adolescent in Banjarmasin. Keywords: Myofascial Pain, Stress, Temporomandibular disorder (TMD).